(untitled) (Lex localis - Journal of Local Self-Government, 2024)
This paper explains how to develop community leaders and elders of the Tha Fa Tai community, Chiang Muan District, Phayao Province of Thailand into the village innovators in managing sustainable community debt and dispute resolution. The Active Learning methods and other community legal teaching innovations, such as law handbooks for drafting wills, debt management, and community mediation, were used in the workshop to provide the participants with the basic legal knowledge relating to debt management and community mediation process. The researcher also worked with the local weavers to adapt the traditional fabric pattern. By the end of this project, the community were expected to self-reliant and sustainably manage debt and reduce disputes, which consequently lowered the cost of traveling and court proceedings by at least 10 per cent.